"Rød og hvid i Billedsalen." Grundtvigs døds- og mindedigte I - Nielsen-Lundgreen, Flemming (Grundtvig-studier, 1980)
“ Red and White in the Picture Gallery” Grundtvig’s memorial poems (I)By Flemming Lundgreen-Nielsen The author sets out to examine six of Gr.’s memorial poems viewed as a particular literary genre within Gr.’s writings. The first part of the essay treats three poems. “ My Mother” (1822) demonstrates how Gr. is able to turn his private grief for his mother’s death into hope for a future renewal of Danish history, poetry and Christianity, not least through Gr.’s own promised efforts. Poetically the poem relies principally on spiritual interpretations and ambiguous considerations of different details around his mother’s death and burial. “ The Birthday (at Gisselfeld, June 11.)” (1823) commemorates Gr.’s supposed patron of literature, Count C.C.S. Danneskiold-Samsøe. The poem is shown to be effective in attaching the manor and park to elements of old Norse mythology, but it is pointed out that in the end the poem fails to bring solace to the widow and her daughters and hardly even convinces the poet himself, the reason being Gr.’s refusal to acknowledge the death of Danneskiold. Finally in “ Jens Baggesen” (1826) Grundtvig as an honest enemy praises and critically characterizes his old opponent and ally, Jens Baggesen. Baggesen’s unfortunate attraction to German language and literature is in Gr.’s opinion more than counterbalanced by his essentially Danish childlike tone, cunning and innocent at the same time, and can be conceived of as evidence of a spiritual attitude to life that may secure Baggesen a revival and a part in the future national life in Scandinavia.The second part of the paper will be published in the 1981 volume.